Intentional and unintentional misbehaving node detection and prevention in mobile ad hoc network. Issue 2 (5th November 2019) - Mohammad, Arshad Ahmad Khan; Mahmood, Ali Mirza; Vemuru, Srikanth
Adaptation and self-forming are the two main qualities of MANET that create various types of sensitive and critical applications, and a single incorrect message may directly or indirectly affect human life. Hence, data communication in this area should be secure. Routing protocol establishes Route selection in MANET based on the assumption that all the nodes present in a network are cooperative, but this assumption is not valid in a hostile environment. Misbehaving activities in network layer are caused by packet drop or refusal to forward the packets by intermediate nodes. However, packets may also be dropped by intermediate nodes due to constrained resources. In this paper, initially we study the routing misbehaviour activities in MANET. Further we propose the mechanism to determine and mitigate the malicious node accurately. Analytical and simulation results show that the proposed work mitigates misbehaving node with less overhead in comparison with existing work.